Dinamika Perdagangan di Pasar Terapung Kalimantan: Dampak Aktivitas Kemaritiman terhadap Struktur Pasar Tradisional - Meyliana Natasyha Nitia Chandra; Agus Salim (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Floating markets in Kalimantan have been an integral part of the traditional trading system in the region. Maritime activities play an important role in supporting the sustainability of these markets as they connect local traders to different regions in the archipelago through waterways. This article examines the dynamics of trade in floating markets, focusing on how changes in maritime activities can affect traditional trade structures and patterns. Modernization of sea transportation and competition from land-based markets have successfully affected the competitiveness of waterborne traders. Therefore, the article also discusses the challenges faced by traders, such as limited access to suitable maritime infrastructure and changing consumer preferences. The research suggests that while floating markets continue to play an important role in the local economy, pressures from globalization and changes in maritime governance may threaten their sustainability.